Utilizing Digital Platforms for the Preservation and Promotion of Traditional Culinary Arts As A Community Empowerment Tool - Maria Lindström; Johan Nilsson; Ingrid Olsson (Pengabdian: Jurnal Abdimas, 2026)
Traditional culinary arts represent not only gastronomic heritage but also local identity and economic potential for communities. However, globalization and rapid changes in consumption patterns have contributed to a gradual decline in cultural food practices, especially in rural areas. Digital platforms offer new opportunities to preserve, promote, and commercialize traditional cuisines while strengthening community participation in the cultural economy. This study aims to examine how digital platforms can be effectively utilized to document culinary heritage, enhance market visibility for local food artisans, and foster sustainable community empowerment. A mixed-method approach was employed, combining qualitative interviews with culinary practitioners and tourism stakeholders, along with observational analysis of digital content and online engagement metrics. The findings reveal that digital platforms particularly social media, e-commerce applications, and online storytelling tools play a significant role in revitalizing traditional culinary knowledge, expanding product reach to broader markets, and increasing income opportunities for local communities. However, inconsistencies in digital literacy and limited access to technology remain significant constraints. The study concludes that integrating digital strategies into cultural food preservation programs can strengthen community resilience while ensuring the continuity of culinary heritage across generations. A collaborative ecosystem involving local governments, educational institutions, and technology providers is necessary to optimize digital empowerment outcomes. Future studies are encouraged to explore scalable models for digital culinary entrepreneurship to support sustainable cultural economy development.